2011
DOI: 10.2310/jim.0b013e31822a24f7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Wilms Tumor 1 (WT1) Gene Transcripts in Egyptian Acute Lymphoblastic Leukemia Patients

Abstract: BackgroundAccurate assessment of minimal residual disease (MRD) in acute lymphoblastic leukemia (ALL) patients after initial chemotherapy is essential to evaluate the efficacy of therapeutic regimens. Wilms tumor 1 (WT1) is a pan-leukemic marker used for identification of the leukemic clone rather than the use of individual specific molecular aberration of ALL.MethodsUsing a real-time quantitative polymerase chain reaction, bone marrow samples from 41 newly diagnosed Egyptian ALL patients; 22 adults and 19 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Our findings in B-cell ALL fit in with the results of recent large-scale studies [12][13][14], including the observation that a sudden increase in WT1 expression seems to be associated with an increased risk of relapse. However, our results in ALL represent only a minor contribution to previous reports, since our sample size was relatively small.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings in B-cell ALL fit in with the results of recent large-scale studies [12][13][14], including the observation that a sudden increase in WT1 expression seems to be associated with an increased risk of relapse. However, our results in ALL represent only a minor contribution to previous reports, since our sample size was relatively small.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, some results have been reported in childhood and adult ALL as well. These suggest that while WT1 expression is not a reliable marker of prognosis and minimal residual disease in ALL, WT1 could still become a therapeutic target, as its overexpression was detected in a sufficiently high number of cases [12][13][14]. For the majority of lymphomas, however, no studies have been published to report the possible prognostic significance of WT1 expression, even though a putative role of WT1 in their pathogenesis has been suggested, much like in acute leukemias [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we found that the WT1 transcript level at diagnosis was significantly associated with CIR, RFS and OS in adult B-ALL patients who received chemotherapy only and patients without BCR-ABL fusion and KMT2A rearrangements. Although others have studied the prognostic effect of the level of WT1 at diagnosis in patients with ALL, the results have been controversial; some studies reported that high WT1 transcript levels were associated with a good outcome [14,21], while some reported the opposite result [15,17,20], and others revealed no independent prognostic role of WT1 transcript levels for DFS and OS [12,13,16,18]. These studies included diverse populations and were not restricted to adult B-ALL patients, especially those who received chemotherapy only.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether WT1 transcript levels at the time of diagnosis can predict outcomes in AML patients is still controversial [6][7][8][9][10][11]. The prognostic role of WT1 in ALL is even less clear and more controversial than its role in AML [12][13][14][15][16][17][18][19][20][21]. This indicates that the mechanism of action of WT1 is complex and that WT1 may play the role of an oncogene or a tumor suppressor gene in different tumors or different subgroups of tumors.…”
Section: Introductionmentioning
confidence: 99%